En Face Optical Coherence Tomography Imaging Ellipsoid Zone Regeneration in Laser-Induced and Solar Maculopathies. (21st November 2019) - Gunzinger, Jeanne M.; Fasler, Katrin; Barthelmes, Daniel; Maloca, Peter; Hasler, Pascal W.; Böni, Christian; Zweifel, Sandrine A.
Abstract : The purpose of the study was to analyze imaging findings in spectral domain en face optical coherence tomography (SD OCT) in patients with laser‐induced and solar maculopathies focusing on the possible regeneration of the ellipsoid zone. In a retrospective case series of 3 patients (4 eyes) with solar maculopathy and 2 patients (3 eyes) with laser‐induced maculopathy who underwent a comprehensive ocular examination, ellipsoid zone (EZ) was segmented from SD OCT data. Evaluation of EZ in en face OCT revealed a hyporeflective lesion surrounded by a hyperreflective border. The area of EZ alteration was measured manually in en face OCT. All patients showed partial EZ regeneration. Mean EZ alteration decreased from 0.12 mm 2 (range: 0.05–0.32) at baseline to 0.07 mm 2 (range: 0.01–0.22) at last follow‐up (p = 0.018, mean follow‐up: 372 days; range: 115–592). Mean best visual acuity (BVA) improved from 20/36 at baseline to 20/30 (p = 0.018 ). In conclusion, en face OCT imaging clearly delineated the area of EZ alteration in patients with laser‐induced and solar maculopathies. Follow-up showed significant reformation of the EZ as well as improvement of BVA.